2012
DOI: 10.1002/path.4105
|View full text |Cite
|
Sign up to set email alerts
|

Clonal evolution of high‐grade serous ovarian carcinoma from primary to recurrent disease

Abstract: High-grade serous carcinoma (HGSC) is the most common and fatal form of ovarian cancer. While most tumours are highly sensitive to cytoreductive surgery and platinum- and taxane-based chemotherapy, the majority of patients experience recurrence of treatment-resistant tumours. The clonal origin and mutational adaptations associated with recurrent disease are poorly understood. We performed whole exome sequencing on tumour cells harvested from ascites at three time points (primary, first recurrence, and second r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
87
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 93 publications
(100 citation statements)
references
References 47 publications
12
87
1
Order By: Relevance
“…Chromosomal instability predicts drug resistance and poor prognosis in multiple cancer types , McGranahan et al 2012 with several recent studies demonstrating the impact of chromosomal instability, tumour heterogeneity and clonal evolution on chemotherapy resistance and metastasis (Bakhoum et al 2011, Gerlinger et al 2012, McGranahan et al 2012, Bashashati et al 2013, Castellarin et al 2013, Murugaesu et al 2015, Jamal-Hanjani et al 2017. Chromosomal instability thus renders tumours more difficult to treat, but precise reasons for this are currently poorly defined.…”
Section: Cin: a Clinical Problemmentioning
confidence: 99%
“…Chromosomal instability predicts drug resistance and poor prognosis in multiple cancer types , McGranahan et al 2012 with several recent studies demonstrating the impact of chromosomal instability, tumour heterogeneity and clonal evolution on chemotherapy resistance and metastasis (Bakhoum et al 2011, Gerlinger et al 2012, McGranahan et al 2012, Bashashati et al 2013, Castellarin et al 2013, Murugaesu et al 2015, Jamal-Hanjani et al 2017. Chromosomal instability thus renders tumours more difficult to treat, but precise reasons for this are currently poorly defined.…”
Section: Cin: a Clinical Problemmentioning
confidence: 99%
“…Patients had a diagnosis of HGSC and underwent standard treatment consisting of surgery followed by carboplatin-based chemotherapy with or without paclitaxel. Further clinical details can be found in our previous publication (31).…”
Section: Patients Biospecimens and Clinical Datamentioning
confidence: 99%
“…We recently performed whole exome sequencing of matched primary and recurrent tumor samples from 3 patients with HGSC (31). By comparing samples collected at primary surgery, first recurrence, and second recurrence, we showed that the HGSC mutanome evolves over time, likely reflecting the growth dynamics of different tumor cell subpopulations, as well as the acquisition of new mutations during chemotherapy.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, HGSC exhibits a high degree of spatial heterogeneity involving potentially dozens of genomically distinct subclones with extensive dissemination across metastatic sites (5-7). Although HGSC is highly sensitive to primary platinum-based chemotherapy, the development of chemoresistant disease is common and can bring profound changes in subclonal architecture and mutation profiles (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%